INVENTARISASI KEBERADAAN DAN PENYEBARAN JEJAK MACAN TUTUL (Panthera pardus melas Curvier, 1809) DI HUTAN LINDUNG CIJAMBU KABUPATEN SUMEDANG) - Reni Srimulyaningsih; Egi Prayoga (Wanamukti: Jurnal Penelitian Kehutanan, 2018)
Leopard (Panthera pardus melas Curvier, 1809) is an endangered species that have been protected because of the population decreased and some population extinct locally. One of them is leopard in Protected Forest Cijambu that no has data about leopard of existence. The objective of this research was to inventory leopard existence and to know distribution of leopard in Cijambu Protected Forest. The method of research is Local community interview and identify of leopard footprint by observation and spatial analysis. The research showed that leopard existence by footprint, feces, scratches, and sound. So, estimate individu of leopard in Cijambu Protected Forest is 3 individual, with a footprint the size of front and rear at 1 individual is 7.5 cm and 7 – 7.1 cm, 1 individu is 11 cm and 10.2 – 10.3 cm, and 1 individual is 6.5 cm and 5.0 cm. Distribution of footprints leopards in Protected Forests Cijambu is exist in Block Legok honje, Pasir panjang, Gunung putri, Gunung sanggara, Bewak and Pangauban.